OpenStudy (anonymous):

Let f(x) = 3x+2 and g(x) = x^2 Part 1 Find f(g(x)) Part 2 Find g(f(x)) Let f(x) = 3x+2 and g(x) = x^2 Part 1 Find f(g(x)) Part 2 Find g(f(x)) @Mathematics

6 years ago
OpenStudy (anonymous):

Is part 1: 3x^2 + 2 Part 2: 6x^2 + 12x + 4?

6 years ago
OpenStudy (anonymous):

f(g(x)) means substitute the full function of g(x) for wherever there is x in f(x). Same with g(f(x)).

6 years ago
OpenStudy (anonymous):

For example: f(gx)) = 3 * (x^2) + 2

6 years ago
OpenStudy (anonymous):

So is my answer right?

6 years ago
OpenStudy (anonymous):

Yes!!

6 years ago